Reorientasi Manajemen Hibah Sanggar Kebudayaan Berbasis Kolaborasi Menuju Penguatan Ekosistem Ekonomi Warga - Rakhman, Arif Kurniar (Universitas Proklamasi 45, 2025)
The management of cultural facilities and infrastructure grants is very important for preserving culture and improving community welfare. Unfortunately, currently this management still targets a single recipient, so the economic results obtained are not yet optimal. The purpose of this study is to examine how culture grant management based on cultural centres can improve community welfare. This study uses a mixed approach and collects data through document analysis and focus group discussions. The research sample was determined using purposive sampling, involving cultural centre managers and related parties. The results of the study show that cultural grant management that is not yet carried out collaboratively limits the potential of grants to have an impact on the economy and community welfare. This study recommends a cultural grant management model based on a collaborative ecosystem. This model involves cultural centres and partner management institutions with the aim of strengthening the cultural value chain and increasing the public benefits of cultural grants.